2010
DOI: 10.1097/wnq.0b013e3181dcebd5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Aneurysmal Subarachnoid Hemorrhage and Analysis of Factors Involved in Early Aneurysm Rebleeding

Abstract: Background and Objectives: The incidence of subarachnoid hemorrhage (SAH) has been very low in earlier studies conducted at Shiraz University compared with reports in the literature. We determined the incidence in our study and compared it to an earlier study and international statistics. In the other part of our study, we examine the factors that contribute to the rerupture of cerebral aneurysms.Method: During 3 years from 2006 to 2009 (1385 to 1388), we handled 230 subarachnoid hemorrhage patients referring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Mortality rate, once reported to be as high as 40%,[1] and later calculated to be about 20%, is now reported to be about 14%, regardless of the significant increase in the number of high-grade patients (Hunt and Hess grade 4 and 5). Acute phase rebleeding used to occur in 10.5% of patients[1] while the incidence is now 1-2%, occurring most commonly in patients who have been referred with delay after 72 h. Interestingly, a significant number of rebleeding cases have occurred at the time or just before craniotomy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality rate, once reported to be as high as 40%,[1] and later calculated to be about 20%, is now reported to be about 14%, regardless of the significant increase in the number of high-grade patients (Hunt and Hess grade 4 and 5). Acute phase rebleeding used to occur in 10.5% of patients[1] while the incidence is now 1-2%, occurring most commonly in patients who have been referred with delay after 72 h. Interestingly, a significant number of rebleeding cases have occurred at the time or just before craniotomy.…”
Section: Resultsmentioning
confidence: 99%
“…[2125] An earlier study performed in our department showed that the rate of SAH was approximately one per 100,000 population. [133] New data suggest an annual rate of 2 per 100,000, which is still much less than the reported worldwide rate of 10 per 100,000. [25] Such an increase is mainly due to better diagnosis and referral.…”
Section: Discussionmentioning
confidence: 99%